KARAKTERISTIK OSEANOGRAFIS DAN PENGARUHNYA TERHADAP DISTRIBUSI DAN TUTUPAN TERUMBU KARANG DI WILAYAH GUGUSAN PULAU PARI, KABUPATEN KEPULAUAN SERIBU, DKI JAKARTA - , DIRGA DANIEL ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Pari Island is part of a cluster of the Seribu Islands which are administratively located in the Thousand Islands District, Jakarta Province. The ecology of Pari Island has a fairly extensive coral reefs. Coral reefis ecosystem that are important for marine life. Changes in oceanographic condition may affect the growth and disitribution of coral reef. Oceanographic parameters such as current, brightness, salinity and temperature can be used as a key to determine the effect of this shifting condition. The purpose of this research is to know the characteristic of oceanographic, to know distribution and lifeform of coral reef and analyis the relation both of them. Oceanographic parameters include brightness, salinity and temperature, while the condition of coral reef cover can be known with the line intercept transect method. The results of measurements of oceanographic parameters are classified into three classifications which compatibleto the requirements of coral growth, and then overlay the map of the classifications. The overlay result show that the waters in the east is most compatibleforthe growth of coral, while on the inside of reef edge and in lagoon is less compatible. Based on the results of image processing Landsat 8 , the most extensive coral distribution is located on the eastern and northern zone. The best coral growth based on transect lines located in the southern region at a depth of 7 meters with a percentage of hard coral cover by 80%, while the lowest percentage of hard coral cover is in the southern region into 4 meters at 35.33%. The influence of the environment in which to live and be accepted by the environmental pressure causes the varies growth and distributionof coral reefs